Why do we discriminate? The role of motivated reasoning - Markus Eyting (Leibniz Institute for Financial Research SAFE, 2022)
Identifying the cause of discrimination is crucial to design effective policies and to understand discrimination dynamics. Building on traditional models, this paper introduces a new explanation for discrimination: discrimination based on motivated reasoning. By systematically acquiring and processing information, individuals form motivated beliefs and consequentially discriminate based on these beliefs. Through a series of experiments, I show the existence of discrimination based on motivated reasoning and demonstrate important differences to statistical discrimination and taste-based discrimination. Finally, I demonstrate how this form of discrimination can be alleviated by limiting individuals' scope to interpret information.
Keywords: D90; J71; D83; 330; discrimination; belief formation; motivated reasoning